The otolaryngologic manifestations of Sotos syndrome 1: A systematic review. (April 2021) - Danis, David O'Neil; Bodamer, Olaf; Levi, Jessica R.
Abstract: Objectives: Sotos syndrome 1 (SOTOS1; MIM:117550) is rare genetic disorder characterized by excessive physical growth before and after birth, distinctive facial features, a large and elongated head, and intellectual disability (Sotos et al., 1964; Tatton-Brown et al., 1993). This systematic review aims to determine otolaryngologic conditions and complications of SOTOS1 based on existing literature through a review of current and past case reports and studies regarding SOTOS1. Methods: A systematic review of all published literature (1964–2020) describing otolaryngologic conditions and/or complications of patients with SOTOS1. Twenty journal articles met inclusion criteria. These articles included 160 patients diagnosed with SOTOS1. Results: Of the 160 individuals with SOTOS1 included in this review, 22 (14%) were reported to have otologic conditions. 4 (3%) individuals were reported to have conditions involving the thyroid and parathyroid glands. 2 (1%) individuals were reported to have head & neck tumors. 39 (24%) individuals were reported to have congenital malformations or abnormalities of the head & neck. 47 (29%) individuals were reported to have feeding difficulties. 16% of individuals were reported to have other otolaryngologic conditions. Conclusions: Our review found multiple otolaryngologic conditions present in patients with SOTOS1, including hearing loss, otitis, hyperthyroidism, hypothyroidism, head & neck tumors, congenital malformations (high arched palate, cleft lip and palate, macroglossia), feeding difficulties, respiratory difficulties, and speech disorders. Additional studies should be conducted to further assess these associations.